Ground-based Observations of Arctic O***sub3*** Loss During Spring and Summer 1997 - Toon, G.; Blavier, J. F.; Sen, B.; Salawitch, R.; Osterman, G.; Notholt, J.; Rex, M.; McElroy, C.; Newman, P.; Russell, J. III (2004)
Ground-based solar absorption spectra were measured from Fairbanks, Alaska (65 degrees North, 148 degrees West) and from Ny Alesund, Spitsbergen, (79 degrees North, 12 degrees East) from March to September 1997 by Fourier Transform Infra-Red (FTIR) spectrometers.